Pengaruh Karakteristik Wirausaha dan Pengetahuan Kewirausahaan terhadap Keberhasilan Usaha (Studi Kasus UMKM di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang) - Pawestri, Maulida Calvica; Batubara, Dedi Iskandar (Regress: Journal of Economics & Management, 2023)
This study aims to determine the effect of entrepreneurial characteristics and entrepreneurial knowledge on business success (Case Study of MSMEs in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency). The population in this study were 78 SMEs in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency. Sample management uses a saturated sampling formula, namely taking the entire population to be used as a sample so that a sample of 78 is obtained. Data collection techniques using documentation, interviews and questionnaires. The classic assumption test used is the Normality Test, Multicollinearity Test and Heteroscedasticity Test. Data analysis using Multiple Linear Regression Analysis technique. The results of this study indicate that entrepreneurial characteristics and entrepreneurial knowledge variables influence business success (Case Study of MSMEs in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency). The results of this study also show that the variable entrepreneurial characteristics and entrepreneurial knowledge simultaneously influence business success (Case Study of MSMEs in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency).